Balance Dysfunction in Parkinson’s Disease: The Role of Posturography in Developing a Rehabilitation Program - Davide Ferrazzoli; Alfonso Fasano; Roberto Maestri; Rossana Bera; Grazia Palamara; Maria Felice Ghilardi; Gianni Pezzoli; Giuseppe Frazzitta (Parkinson's Disease)
Balance dysfunction (BD) in Parkinson’s disease (PD) is a disabling symptom, difficult to treat and predisposing to falls. The dopaminergic drugs or deep brain stimulation does not always provide significant improvements of BD and rehabilitative approaches have also failed to restore this condition. In this study, we investigated the suitability of quantitative posturographic indicators to early identify patients that could develop disabling BD. Parkinsonian patients not complaining of a subjective BD and controls were tested using a posturographic platform (PP) with open eyes (OE) and performing a simple cognitive task [counting (OEC)]. We found that patients show higher values of total standard deviation (SD) of body sway and along the medio-lateral (ML) axis during OE condition. Furthermore, total and ML SD of body sway during OE condition and total SD of body sway with OEC were higher than controls also in a subgroup of patients with normal Berg Balance Scale. We conclude that BD in Parkinsonian patients can be discovered before its appearance using a PP and that these data may allow developing specific rehabilitative treatment to prevent or delay their onset.